Trimester-Specific Weight Gain and Midpregnancy Diastolic Blood Pressure Rebound During Normotensive Pregnancy. Issue 4 (October 2017) - Lei, Qiong; Zhou, Xin; Duan, Dong-Mei; Lv, Li-Juan; Lin, Xiao-Hong; Ji, Wen-Jie; Cai, Wei; Zhang, Zhuoli; Li, Yu-Ming; Niu, Jian-Min
Abstract : The longitudinal exposure–response relationship between trimester-specific gestational weight gain (GWG) and blood pressure (BP) during pregnancy is not well understood. We retrospectively assessed 1112 uncomplicated, normotensive pregnant women whose body weight and BP were measured from 12 +0 to 40 +0 weeks of gestation from a hospital-based cohort. By using growth curve modeling, a J-shaped pattern dominated diastolic BP (DBP) changing dynamics, with a midpregnancy drop at 20 +0 to 22 +0 weeks followed by a rebound. Using group-based trajectory modeling, 3 distinctive trajectories of DBP were identified: high–J shaped (18.5%), moderate–J shaped (48.3%), and low–J shaped (33.1%), as well as 3 distinctive GWG trajectories: high increasing (14.7%), moderate increasing (48.6%) and low increasing (36.8%). A temporal coincidence between the maximal rate of GWG and DBP transition from its nadir to rebound was observed during 20 +0 to 22 +0 weeks. Moreover, women in the high-increasing GWG group had the highest probability of being in the high–J DBP group. The GWG rate during the late midsecond trimester (22 +0 to 26 +0 weeks) was consistently associated with an elevated DBP level: for every 200 g/wk increase, the multivariable-adjusted odds ratio was 1.27 (95% confidence interval, 1.13–1.43) for the trajectory shift to the high–J group and 1.20 (95% confidence interval, 1.07–1.35) for the occurrence of diastolic prehypertension after 37 +0 weeks. Furthermore, adding a trimester-specific GWG rate (22 +0 to 26 +0 weeks) contributed to the incremental yield for the prediction of diastolic prehypertension after 37 +0 weeks. Our results thus provide the timing and extent of gestational weight control relevant to the optimized BP level during pregnancy. Abstract : Supplemental Digital Content is available in the text.